Pengaruh Penerapan Model Project Based Learning (PJBL) Terintegrasi STEAM (Science, Technology, Engineering, Art, and Mathematics) Terhadap Kreativitas Siswa - Rahman, Abdul; Jana, Nur; Asdar, Asdar (Issues in Mathematics Education (IMED), 2025)
Four basic skills (4Cs) are essential for the 21st century, one of which is creativity and innovation. However, in reality, the level of creativity in Indonesia remains relatively low. To address this issue, it is necessary to implement appropriate learning activities to enhance students' creativity. One of the effective approaches is the application of the Project-Based Learning (PjBL) model integrated with STEAM (Science, Technology, Engineering, Arts, and Mathematics). This study aimed to determine whether students' creativity with the application of the Project-Based Learning (PjBL) model integrated with STEAM was more creative compared to the creativity of students with the application of the Project-Based Learning model without STEAM integration. This research employs a quantitative approach using a quasi-experimental method. The independent variables in this study are the STEAM-integrated PjBL model and the PjBL model without STEAM integration, while the dependent variable is students' creat. This research was a quantitative study using a quasi-experimental method. The independent variables in this study were the Project-Based Learning model integrated with STEAM and the Project-Based Learning model without STEAM integration, while the dependent variable was students' creativity. The data in this study were obtained by assigning projects in the form of a post-test (performance assessment and product assessment). The data analysis technique in this study was divided into two parts: descriptive statistical analysis and inferential statistical analysis, specifically simple linear regression tests and independent sample t-tests.